2022
DOI: 10.3390/brainsci12030358
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibrotactile Biofeedback Providing Real-Time Pressure Information on Static Balance Ability and Weight Distribution Symmetry Index in Patients with Chronic Stroke

Abstract: Training with visual and auditory biofeedback, in patients with stroke, improved balance ability and asymmetric posture. We developed a new biofeedback training device to prevent falls and improve balance ability in patients with stroke. This device corrects motion errors by collecting the pressure information of patients in real-time. This randomized crossover study aimed to investigate the effect of this biofeedback training on the static balance ability and weight distribution symmetry index in 24 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Another example is wearable focal stimulation devices, such as a vibrotactile glove (VTG), which provides vibratory input to the paretic limb of chronic stroke survivors and has been shown to promote neural plasticity and reduces spasticity [ 44 , 45 ]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is wearable focal stimulation devices, such as a vibrotactile glove (VTG), which provides vibratory input to the paretic limb of chronic stroke survivors and has been shown to promote neural plasticity and reduces spasticity [ 44 , 45 ]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…VTGs provide vibratory input to the paretic limb of chronic stroke survivors and have been shown to promote neural plasticity and reduce spasticity [45,46]. Other studies have used robot-assisted somatosensory training and vibrotactile biofeedback devices [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…12 The dual-task paradigm has been used to investigate the cognitive demand of postural control by examining how postural stability is affected when a postural task is performed concurrently with a cognitive task in numerous studies in healthy young and older people adults and patients with neurological disorders. 13,14 Several studies have compared the performance between young adults and the elderly in dual-task situations to evaluate the role of aging in integrating visual information for postural control. Despite an overall increase in postural sway with aging, these dual-task studies have shown that the visual contribution to postural control remains relatively unaffected by age.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is expected that simultaneously performing cognitive and postural tasks would decrease the available attentional resources for postural control, leading to a decrease in postural stability 12 . The dual‐task paradigm has been used to investigate the cognitive demand of postural control by examining how postural stability is affected when a postural task is performed concurrently with a cognitive task in numerous studies in healthy young and older people adults and patients with neurological disorders 13,14 …”
Section: Introductionmentioning
confidence: 99%